Antioxidant and anti-cancer cell proliferation activity of propolis extracts from two extraction methods - Supakit Khacha-ananda (2018)
Antioxidant activity, total phenolic, total flavonoid compounds and cytotoxicity to cancer cell lines of propolis extracts from two extraction methods were investigated in this study. Propolis was collected from Phayao province and extracted with 70% ethanol using maceration and sonication techniques. The antioxidant activity was evaluated by DPPH assay. Total phenolic and flavonoid compounds were also determined. Moreover, the cytotoxicity of propolis was evaluated using MTT assay. The percentage propolis yield after extraction using maceration (18.1%) was higher than using sonication (15.7%). Nevertheless, antioxidant and flavonoid compounds of the sonication propolis extract were significant greater than using maceration. Propolis extract from sonication showed antioxidant activity by 3.30±0.15 mg gallic acid equivalents/g extract. Total phenolic compound was 18.3±3.30 mg gallic acid equivalents/g extract and flavonoid compound was 20.49±0.62 mg quercetin/g extract. Additionally, propolis extracts from two extraction methods demonstrated the inhibitory effect on proliferation of A549 and HeLa cancer cell lines at 24, 48 and 72 hours in a dose-dependent manner. These results are of interest for the selection of the most appropriate method for preparation of propolis extracts as potential antioxidant and anticancer agents.